A Feasibility Investigation of Laboratory Based X-ray Absorption Spectroscopy in Support of Nuclear Waste Management. (2020) - Mottram, L.M.; Wilkins, M.C. Dixon; Blackburn, L.R.; Oulton, T.; Stennett, M.C.; Sun, S.K.; Corkhill, C.L.; Hyatt, N.C.
ABSTRACT: X-ray Absorption Spectroscopy is a technique of fundamental importance in nuclear waste management, as an element specific probe of speciation, which governs radionuclide solubility, immobilisation and migration. Here, we exploit recent developments in laboratory instrumentation for X-ray Absorption Spectroscopy, based on a Rowland circle geometry with a spherically bent crystal analyser, to demonstrate speciation in prototype ceramic and glass-ceramic waste forms. Laboratory and synchrotron XANES data acquired from the same materials, at the Ce and U L3 edges, were found to be in excellent quantitative agreement. We establish that analysable laboratory XANES data may be acquired, and interpreted for speciation, even from quite dilute absorber concentrations of a few mol%, albeit with data acquisition times of several hours. For materials with suitable absorber concentrations, this approach will enable routine element specific speciation studies to support rapid optimisation of radioactive waste forms and analysis of radiological materials in a purpose designed laboratory, without the risk associated with transport and manipulation at a synchrotron radiation facility.